Using APV: a better tool for valuing operations - Luehrman, Timothy A. (2007)
One of the most disseminated ways of valuing operating assets is discounted Cash flow, or DCF. But weighted average cost of capital, or WACC - one of the most commonly accepted forms of DCF - has become obsolete. This article discusses an alternative to WACC known as adjusted present value, or APV. The article shows that this new methodology is greatly superior to WACC, due specially to the fact that it provides additional managerially relevant information at lower error levels, helping executives determine not only how much an asset is worth, but also where its value comes from.